Jernaldergrave ved Gjurup med teltformede dødehuse - Friis, Palle (Kuml, 1963)
Iran-Age graves at Gjurup with tent-shaped "grave-houses" To the south of the Løkken road, between Gjurup and Hjørring in Vendsyssel (North Jutland), lies a low hill running WNW-SSE (Fig. 1). The hill is part of Peter Olsen's farm and, in the spring of 1960, after he had twice seen his new-sown corn, together with the fine surface sand of his field, blown over the hedge to his neighbour by the spring storms, he decided to lay the hill down to grass. In doing so he struck stones, and spadework revealed a finely built stone cist. As two similar cists were known to have been found in 1924 close by there was a good chance for further graves, and Peter Olsen gave Hjørring Museum permission to dig at will the following summer in his field. These months produced a total of 42 Iron-Age graves. Only the 3 graves already known, which lay on the top of the hill (Fig. 2), were of stone, the remaining 39 being completely without stones. There are signs here and there that the graves lie in rows following the axis of the hill. The eastern limits of the cemetery could not be ascertained, as here a road intervenes. Concerning the two stone-built graves from 1924 the scanty information available suggests only that both were built up of two courses of stone but that only the westermost (no. 2) had its roof slabs preserved. The roof of the grave from 1960 (no. 3) was completely intact (Fig. 3). The chamber, 90X160 cms. in size, was bounded by two courses of large stones, the upper course projecting inwards to reduce the width at the top to about 60 cms. In this grave sufficient of the skeleton survived for it to be seen that the body lay on its side, in flexed position, along the south side of the grave. The head was in the west, with face to the north (Fig. 4). In the chamber's west end stood t wo pottery vessels, and a third stood by the centre of the north wall, together with 9 small stones. Also by the north wall and level with the shoulder of the body lay a one-edged knife of iron and the rib of a deer. The 39 earth graves were almost uniform, rectangular, often with rounded corners, vertical walls and flat bottom. The size varied considerably, from 100 to 230 cms. in length, from 70 to 200 cms. in width. 6 graves were so small that they cannot be other than those of children. The bodies lay in every case in the southern half (unlike the burial custom of central Jutland), but in 12 cases with the head to the east and in 18 with the head to the west. The number of pottery vessels varied from 8 to none. Iron eating knives were found in 27 graves, dress-pins in 2, and beads of amber or glass in 5. Small stones, varying from 4 to 16 in number, were found in 15 graves, either in a little heap on the grave floor or in the bottom of a pot. Their significance is still unknown. Figs. 5 and 6 show a typical grave (no. 11), with the grave gifts by the north wall, and with a circular posthole, about 30 cms. deep, at each end of the grave. Such postholes are common in the earth-graves of Vendsyssel, and have long been interpreted as evidence of roofing above the graves. A number of lengthwise and crosswise sections through the Gjurup graves, where the postholes where found in 26 graves and where conditions of preservation were good, enables us now to explain, and illustrate, the greater part of the tent-like roofing of the grave (Figs. 5, 7-8, 10-11). On the basis of the excavations we may attempt to form a picture of a burial among the Iron-Age people of Gjurup. The body is placed, together with the gifts that accompany it, in a rectangular excavation about a metre deep. The ceremonies accompanying the burial cannot be reconstructed in detail, but numerous "cooking-pits" around the graves suggest ritual feasts, perhaps "shared« with the dead. Thereafter the vertical end-posts of unshaped wood are set up in the two postholes; they are 10-12 cms. thick and 75-100 cms. high, or about the same as the depth of the grave. On top of the posts, perhaps in a fork, is placed the horizontal beam, probably also unshaped. Rafters, 6-7 cms. thick, are placed in position, leaning against the beam, at intervals of 10-15 cms. How the space between the rafters has been closed is unknown, but firm turves would be quite capable of spanning this interval. Finally the roofing will be covered with the soil dug up from the excavation, so that the grave is marked by a low mound. Pottery vessels buried in these mounds show that offerings of food have also been made after the burial (Fig. 8). Probably some 5-10 years would pass before the rotting of the wood and the weight of the earth above would cause the grave-roof to collapse. Evidence of this collapse can be seen in the section through grave 4 shown in Fig. 9. The grave furnishings of the cemetery tel1 of a simple, almost poverty-stricken community. 4 small uncoloured glass beads and a bronze fibula form the most distinguished set of ornaments found (Fig. 18). A total of 153 pottery vessels were discovered, all, with a few exceptions, traditional Roman Iron-Age pottery. There were normally 2-4 vessels to a grave, but Fig. 12 shows one of the more numerous sets, from Grave 10. Pedestal beakers were found in 9 graves, and 4 of these are shown in Fig. 13, the biconical form, sometimes with pierced foot, being a special Vendsyssel type"). Ornamentation with die-stamps, known from discoveries in various places in Jutland but particularly popular in Vendsyssel 7), can be seen on the little beaker in the foreground, and on this and another vessel in Fig. 14. The vessel shown in Fig. 15 (and in situ in Fig. 4) bears, among other incised decoration, two crescents which may be purely decorative but which it is tempting to interpret as stylized eyes. Several examples of face-urns are known from Vendsyssel 8), while representations of eyes as a religious symbol are known over the greater part of Europe 9). Fig. 16 shows an unusual type of vessel, found in Grave 36 with 6 food vessels. It is spherical, 65 mms. high and with a 4.0 mm. wide opening. About ten vessels with such an opening are known from Vendsyssel, of varying shapes but of much the same size and with the interior only roughly smoothed. They are undoubtedly lamps, using tallow for fuel and elder-pith as a wick. A vessel from Grave 5 (Fig. 17) is completely unique, resembling most closely a modern brazier. Slight marks of wear on the inner sides of the four knobs at the top suggest that it may have had that function. How much, then, do we know of the Iron-Age community at Gjurup? All the objects found belong to the Early Roman Iron Age, and the two fibulae (Figs. 18 and 19) suggest the end of the first half of that period, about 50-100 A. D. 10). Assuming that the cemetery was in use for 100 years, with an average age at death of 30-35 years, we reach a community of about 14 persons, and while there are many unknown factors in this calculation the community can hardly have been larger than a single family unit. The greater number of graves excavated in Vendsyssel have been stone-built, but there is a strong possibility that earth graves are in fact much more numerous. On the occasions when it has been possible to broaden the area of investigation around stone graves earth graves have almost always turned up in considerable numbers. Chronologically there is no difference between the two types, so that the stone graves probably imply a higher social position, a theory supported by the position of the Gjurup stone graves on the top of the hill. The method of roofing the earth graves here described has not yet been registered outside Vendsyssel. The wooden roofing distinguished in several graves in South and East Jutland was rather a lid above the burial chamber 11). The large stone-built graves show that Vendsyssel formed a separate culture-area in the Roman Iron Age, and the special construction of the earth graves adds weight to this view. The pottery indicates a cultural connection with Southeast Germany, where, in the region north of the Alps, we find stone-built graves occurring at the end of the Celtic Iron Age 12). The burial tradition must have reached Vendsyssel by sea, as it is unknown in South Jutland. Palle Friis